2019
DOI: 10.1159/000499766
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-362-3p Targets PAX3 to Inhibit the Development of Glioma through Mediating Wnt/β-Catenin Pathway

Abstract: Background: Glioma is identified as a broad category of brain and spinal cord tumors. MiR-362-3p is important in regulating the genesis of different cancers; however, the mechanism of miR-362-3p in the progression of glioma remains largely unknown. Objectives: This study aimed to elucidate pathobiological functions of miR-362-3p by targeting PAX3 in glioma. Method: qRT-PCR and western blotting were used to examine miR-362-3p and PAX3 expression in glioma tissues and cells. CCK-8 assay and transwell assays were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…MiR-362-3p has been shown to be abnormally expressed in a variety of tumors [21, 22]. For instance, it was reported that miR-362-3p, as a tumor suppressor, inhibited the progression of Glioma by targeting PAX3 and LUAD tumorigenesis by decreasing the E2F1, respectively [23, 24]. RAB23 is an important member of RAS proto-oncogene family and is considered as an tumor promoter [25].…”
Section: Introductionmentioning
confidence: 99%
“…MiR-362-3p has been shown to be abnormally expressed in a variety of tumors [21, 22]. For instance, it was reported that miR-362-3p, as a tumor suppressor, inhibited the progression of Glioma by targeting PAX3 and LUAD tumorigenesis by decreasing the E2F1, respectively [23, 24]. RAB23 is an important member of RAS proto-oncogene family and is considered as an tumor promoter [25].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Xu et al have reported that miR-362-3p expression is decreased in glioma tissues and cells and can suppress the development of glioma. 19 A study by Wang et al reveals the downregulated expression of miR-362-3p in cervical adenocarcinoma tissues and cell lines, and reveals its inhibitory role in cervical adenocarcinoma. 20 In epithelial ovarian cancer (EOC), miR-362-3p levels are low in EOC tissues and cells, and play an anti-proliferative role in EOC.…”
Section: Discussionmentioning
confidence: 99%
“…EMX1 and WASF2 levels should be further explored as potential clinical metrics in SCG for patient stratification and disease prognostication. Considering that the other member of the EMX family of transcription factors, EMX2, has been proposed to as a potential suppressor of GBM cells (Falcone et al., 2016 ; Monnier et al., 2018 ), and the WNT/β‐catenin pathway has been report linking to the malignant phonotype of brain glioma (Fan et al., 2021 ; Xiang et al., 2022 ; Xu et al., 2019 ), the EMX1/WASF2/β‐catenin possibly also can be applied to gliomas occurring in other locations such as the brain. We would like to focus on this issue in the future researches.…”
Section: Discussionmentioning
confidence: 99%